MENGGAGAS DAKWAH KORESPONDENSI NABI MUHAMMAD SAW - Abdul Ghoni (Jurnal Ilmu Dakwah, 2017)
This type of research is qualitative by using historical approach. Technique of collecting data in this research is library research (literature study). The results of the study as follows; the background of sending letters as a medium of propaganda by Rasulullah SAW. to the kings of his time were carried out for several reasons from theological and political aspects. The propagation format of Rasulullah SAW. which was sent to the kings and rulers of the time was astonishing, as evidenced by several things, namely; a). The Prophet's Epistles. always preceded the sentence Basmalah, b) The composition of the sentence in the letter of the Messenger of Allah. always preceded the phrase "From Muhammad the servant of God and his messenger", c). The contents of the letter of the Prophet SAW. worth persuasively invites kings to embrace Islam. From the elaboration of the correspondence of Prophet Muhammad SAW this should da'i be able to apply the information media as part of the dakwah correspondence.